2018
DOI: 10.1186/s13023-018-0858-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of pegvaliase for the treatment of phenylketonuria in adults: combined phase 2 outcomes through PAL-003 extension study

Abstract: BackgroundDeficiency of phenylalanine hydroxylase causes phenylketonuria (PKU) with elevated phenylalanine (Phe) levels and associated neuropsychiatric and neurocognitive symptoms. Pegvaliase (PEGylated phenylalanine ammonia lyase) is an investigational agent to lower plasma Phe in adults with PKU. This study aimed to characterize the long-term efficacy, safety, and immunogenicity of pegvaliase in adults with PKU.MethodsPAL-003 is an ongoing, open-label, long-term extension study of the pegvaliase dose-finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Demographics and baseline characteristics for patients enrolled in the pegvaliase clinical trials have been presented in detail elsewhere. 19 , 21 , 22 , 23 , 24 , 25 , 26 In brief, the 5 studies discussed herein enrolled a total of 337 patients (range per study: 16–261). The range of mean baseline ages was 26.1–32.2 years, body mass index was 26.5–29.5, and blood Phe concentration was 1178.7–1482.1 μmol/L.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Demographics and baseline characteristics for patients enrolled in the pegvaliase clinical trials have been presented in detail elsewhere. 19 , 21 , 22 , 23 , 24 , 25 , 26 In brief, the 5 studies discussed herein enrolled a total of 337 patients (range per study: 16–261). The range of mean baseline ages was 26.1–32.2 years, body mass index was 26.5–29.5, and blood Phe concentration was 1178.7–1482.1 μmol/L.…”
Section: Resultsmentioning
confidence: 99%
“…The methods for studies reported herein were previously published. 19 , 21 , 22 , 23 , 24 , 25 , 26 In brief, PAL‐002 was an open‐label, multicenter, single‐arm phase II study in which pegvaliase was administered via subcutaneous injection in weekly doses of 0.001–0.1 mg/kg/day over an 8‐week induction phase followed by an 8‐week titration phase. 19 , 23 In the open‐label, multicenter phase II PAL‐004 trial, daily doses of 0.06–0.8 mg/kg/day were administered for 13 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Administered by daily subcutaneous injection, pegvaliase circulates in blood and converts Phe to trans-cinnamic acid and ammonia. Several phase 1, 2, and 3 clinical trials have demonstrated the effi cacy of pegvaliase in decreasing blood Phe concentration in adults, even down to the normal range, while liberalizing dietary Phe intake [16][17][18][19] . This revolutionary treatment approach is increasingly available in the US and Europe, yet still demands daily injections and is associated with immune-mediated hypersensitivity reactions in some individuals.…”
Section: Phenylalanine Hydroxylase (Pah) Reaction and Phenylketonurmentioning
confidence: 99%